Self-Concept of College Students: Empirical Evidence from an Asian Setting - Balba, Jonah C.; Caingcoy, Manuel E. (Technium Social Sciences Journal, 2021)
Individuals with high self-concept will likely have high life satisfaction, they easily get adjusted to life, and they communicate their feeling more appropriately. However, it was not certain whether self-concept would decline or improve as individuals age, or whether self-concept would vary between genders and ethnic groups. To prove, a study was carried out to compare the self-concept of college students in an Asian context. The inquiry utilized the cross-sectional design in finding out significant differences in the self-concept of participants in terms of age, gender, and ethnicity. A 22-item questionnaire was adapted and administered to 222 Bachelor of Public Administration and Bachelor of Science in Business Administration students from the satellite campus of Bukidnon State University in the Philippines. Initially, a sample was randomly drawn from the population. During the actual data collection, the researchers had difficulty getting the responses from the randomly selected individuals due to internet connection and it was done amidst a pandemic. Instead, it took all responses from those who were available, have access to the internet, and could accomplish the google forms. The data were analyzed using Mean, Standard Deviation, T-test for independent sample, ANOVA and Post Hoc test. The results revealed that college students at the locale have a high level of self-concept in self-fulfilment, emotional adjustment, and honesty. Yet, they only had a moderate level of self-concept in autonomy. Further, there were significant differences in college students’ autonomy and honesty in terms of age and gender. Furthermore, there were significant differences in their emotional adjustment and self-fulfilment as to their ethnicity. The results have implications for instruction, administration, guidance services, and future research.